Autophagy‐related gene expression regulated by HIF‐1α in salivary adenoid cystic carcinoma. (3rd March 2019) - Liu, Chao; Li, Shengfeng; Pang, Fawei; Wu, Haiwei; Chai, Li; Liang, Cheng; Zhang, Dongsheng
Abstract: Objectives: Salivary adenoid cystic carcinoma (SACC) is one of the most common malignant salivary gland tumors. Our study aims to investigate whether hypoxia‐induced autophagy was up‐regulated in the progression of SACC. Materials and methods: We performed differentially expressed gene analysis and pathway enrichment analysis and then calculated the correlation analysis on GSE59701 and GSE28996 datasets. The expression of HIF‐1ɑ and MAP1LC3B was analyzed in the paraffin‐embedded specimens by immunohistochemical method and in the hypoxic SACC‐LM cells by immunofluorescence. TEM microscopy was also performed to observe the formation of autophagosomes in SACC tissue and the hypoxic SACC‐LM cells. Results: The autophagy pathway was up‐regulated in SACC datasets, and five genes including MAP1LC3B were positively correlated with HIF‐1ɑ. Immunohistochemistry results showed that autophagy was activated and the expression of HIF‐1ɑ and MAP1LC3B was positively correlated in SACC specimens. In hypoxic SACC‐LM cells, we also identified the up‐regulation of autophagy and the close correlation between HIF‐1ɑ and MAP1LC3B expression. Autophagosomes were observed both in the tissue and the hypoxic SACC‐LM cells by TEM microscopy. Conclusions: Our study showed that autophagy is up‐regulated in dataset, SACC tissue, and hypoxic cell line; hypoxia‐induced autophagy in SACC might play a vital role in the development of SACC.